Comparative analysis of the technical and economic feasibility of supplying electricity during peak hours using diesel generation and battery storage systems - Nascimento Neto, Paulo Felix do; Garcia, Altemir Tomaz de Carvalho; Freitas, Isaac Soares de; Salvadori, Fabiano (Brazilian Journal of Production Engineering, 2025)
This paper presents a comparative analysis of the technical and economic feasibility of supplying electricity using Diesel Generation Systems (DGS) and Battery Energy Storage Systems (BESS) during peak hours to reduce energy costs in the University Hospital of the Federal University of Paraíba (UFPB). Data on energy consumption was collected to identify the unit’s consumption profile. The main economic indicators were applied: NPV, payback, IRR and LCOE. The Monte Carlo Simulation (MCS) method was used. Four DGS and four BESS proposals were compared. The best SGD proposal presented the following results: payback of 11.2 years, NPV of R252,109.46, IRR of 15.47% and LCOE of R3,075 and the best BESS proposal, with payback of 9.8 years, NPV of R1,596,671.33, IRR of 17.58% and LCOE of R2,134. SMC obtained the following results: for SGD, there was a 0.8032 probability of the IRR exceeding the Minimum Attractive Rate (MAR). For BESS, the probability of NPV greater than 0 and IRR greater than MAR was equal to 1.